Islamic on using social-net applications - Wan Ab. Rahman, Wan Nurhayati (2012)
Social-net applications have becoming a phenomenon in the borderless Internet network. The exposure, attractiveness and influence of using the social-net applications have tremendously involved individuals of different demographic profiles such as age, race, gender, economic status, education background, income level and employment. However, without any proper guidance of adopting the social-net applications for the right purpose, many individuals have become victims of misuses of social-net applications and cyber crimes. Therefore, this paper particularly highlights the needs of true guidance that is from Islam as the basic to improve knowledge of optimizing benefits from social-net applications. There are good values in Islam such as taqwa, shy, honest, ethic and integrity that could prevent human from doing harms to others including social problem, black mail and cheating especially through the social-net applications.